Ethnic Relationships in Nazi-occupied Lithuania in 1941–1944 - Bubnys, Arūnas (Genocidas ir rezistencija, 2011)
This article is based on documentary materials from various countries and Lithuanian and foreign historiography and analyses ethnic relationships in Nazi-occupied Lithuania in 1941–1944. The author discusses the following three main issues: 1) policies of the Nazi occupiers towards people of different ethnic groups living in Lithuania; 2) reaction of the ethnic groups of the occupied country towards Nazi policies; and 3) mutual relations of different ethnic groups living in Lithuania. The article mostly focuses on ethnic relations in the region of Vilnius.
Keywords: German occupation; ethnical relationship; Polish; Russians; Belarussians